The Evaluation of Anti Microbial Activity of Classical Siddha Medicine Seenthil Choornam - Sunanna, Lalitha; Manoharan, A. (Asian Journal of Pharmaceutical Research and Development, 2022)
Seenthil Choornam is a Classical Siddha medicine having its ingredients with herbal andanimal origin. The raw drugs- Seenthil (Tinospora cordifolia .sp), Karisalai (Ecilpta Albasp), and Poonagam(Eudriluseugeniae.sp) were purified and combined as per theliterature. Aim: - The aim of the study is to evaluate the anti-microbial activity of Seenthil Choornam. Materials and methods: - Raw drugs were collectedfrom Keralaand Tamilnadu .The identification and authentication of plant drugs were obtained fromGovt.Siddha Medical College, Palayamkottai. The authentication of Poonagam (Eudrilus eugeniaesp.) was obtained from Advanced Centre of Environmental Studies and Sustainable Development-Inter University Centre – Mahatma Gandhi University, Kottayam...Anti-bacterial and Anti-fungal activity of aqueous and ethanolic extract of drug is studied for its activity against four Gram positive, three Gram negative bacteria and five fungi in concentrations of 25ul, 50ul, 75ul and 100ul , using Disc diffusion method. The standard drug for comparison of anti-bacterial activity is Streptomycin and for Anti-fungal activityis Fluconazole. Result:- The aqueous extract of drug in concentrations of 75ul & 100ul has zone of inhibition against Bacillus subtilis (G+ve)- (19mm, 21mm) ,Enterococcusfeacalis-(G+ve)in conc.75ul&100ul - (11mm, 13mm), Klebsiella pneumonia (G-ve) in conc.75ul &100ul- (11mm ,13mm) , Staphylococcus aureus (G+ve)in conc. 75ul &100ul-(10mm,11mm) and towards fungus -Aspergillus flavusin conc. 75ul &100ul ( 12mm, 13mm ) .From the above study it is evident that the classical medicineSeenthil Choornamis effective against human pathogens.